2005
DOI: 10.1186/1743-0003-2-20
|View full text |Cite
|
Sign up to set email alerts
|

Gait dynamics in mouse models of Parkinson's disease and Huntington's disease

Abstract: BackgroundGait is impaired in patients with Parkinson's disease (PD) and Huntington's disease (HD), but gait dynamics in mouse models of PD and HD have not been described. Here we quantified temporal and spatial indices of gait dynamics in a mouse model of PD and a mouse model of HD.MethodsGait indices were obtained in C57BL/6J mice treated with the dopaminergic neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP, 30 mg/kg/day for 3 days) for PD, the mitochondrial toxin 3-nitropropionic acid (3NP, 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
104
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(116 citation statements)
references
References 72 publications
9
104
1
2
Order By: Relevance
“…Additionally, these treadmill-based analyses of gait have been conducted within 24 hr of final MPTP injection, whereas the current study examines deficit 10 days later. One acute MPTP study found decreased stride length and increased stride frequency using the DigiGait treadmill, similar to the trend observed in the current study (Amende et al, 2005, their Table 1). Stride duration was decreased to a greater extent in progressively treated MPTP animals compared with these acute studies, resulting in a trend similar to that of acute MPTP treatment but with a significant outcome.…”
Section: Progressive Mptp Leads To Lasting Changes In Multiple Gait Dsupporting
confidence: 93%
See 4 more Smart Citations
“…Additionally, these treadmill-based analyses of gait have been conducted within 24 hr of final MPTP injection, whereas the current study examines deficit 10 days later. One acute MPTP study found decreased stride length and increased stride frequency using the DigiGait treadmill, similar to the trend observed in the current study (Amende et al, 2005, their Table 1). Stride duration was decreased to a greater extent in progressively treated MPTP animals compared with these acute studies, resulting in a trend similar to that of acute MPTP treatment but with a significant outcome.…”
Section: Progressive Mptp Leads To Lasting Changes In Multiple Gait Dsupporting
confidence: 93%
“…Several studies have reported the use of the DigiGait gait analysis system in acutely MPTP-treated mice (Amende et al, 2005;Rommelfanger et al, 2007); however, this is the first report using a progressive paradigm. Additionally, these treadmill-based analyses of gait have been conducted within 24 hr of final MPTP injection, whereas the current study examines deficit 10 days later.…”
Section: Progressive Mptp Leads To Lasting Changes In Multiple Gait Dmentioning
confidence: 95%
See 3 more Smart Citations